Holocene chronology of a continental shelf mudbelt off southwestern Africa - Meadows, M. E.; Rogers, J.; Lee-Throp, J. A.; Bateman, M. D.; Dingle, R. V. (The Holocene, 2002)
The Holocene lithostratigraphy and geochronology of sediments on an inner continental-shelf mudbelt off the west coast of southern Africa is presented. Based on a study of seven large gravity cores, numerous grab samples and two vibracores, two distinctive sections of the mudbelt have been identi” ed. The northern section is associated with the Orange River prodelta, and is dominated by laminated clay-rich sediments, while the southern section off Namaqualand is associated with more homogeneous muds. AMS radiocarbon ages of 31 samples from these cores are problematic due to the absence of expected modern material at the sedimentocean interface and numerous age reversals and inconsistencies in some of the cores. Possible mechanisms to explain the apparently anomalously old surface and near-surface samples are suggested. Most likely expla nations appear to lie in a combination of sediment-retrieval problems, the periodic loss of ” ne particulate organic carbon from within the water column, the sampling of possible relic sediments and, most likely of all, the incorporation into the sediments of 14C-depleted terrigenous organic matter. The age reversals are especially evident in the laminated sediments, and the entrainment of ‘old’ carbon from the terrestrial source of these sediments is offered as the most parsimonious explanation. Stable carbon isotope analyses and a single lumi nescence age support the contention that radiocarbon date inconsistencies are a consequence of terrestrial inputs of carbon which is non-contemporaneous with the actual time of sedimentation. In studies of offshore accumulations of terrigenous material, the marine-derived organic fraction may therefore prove a more reliable measure of radiocarbon chronology.
id: 220

Characterising the Namaqualand mudbelt of southern Africa: chronology, palynology and palaeoenvironments - Gray, C. E. D.; Meadows, M. E.; Lee-Thorp, J. A.; Rogers, J. (South African Geographical Journal, 2000)
id: 219

Radiocarbon chronology of Namaqualand mudbelt sediments: problems and prospects - Meadows, M. E.; Dingle, R. V.; Rogers, J.; Mills, E. G. (South African Journal of Science, 1997)
This paper presents the first radiocarbon-dated chronology of the mudbelt which occupies the continental shelf around southern Africa. The results confirm the Holocene age of the superficial deposits and suggest that laminations in the sediments of the mudbelt off the Orange River mouth are recent and terrestrially derived. Two anomalies are, however, apparent in the chronology. First, the surface sediments do not provide recent or contemporary radiocarbon ages, as would be expected. Second, the laminated sediments yield ages which are not in stratigraphic sequence and appear to be clustered around the period 1000 to 1700 sri Possible reasons for these anomalies are discussed together with alternative means of deriving a more accurate and reliable chronology for the mudbelt sediments.
Yb537Times Cited:7 Cited References Count:18
Keywords: accumulation rates; ages; Marine

Sedimentology of terrigenous mud from the Orange River delta and the inner shelf off Namaqualand, South Africa - Mabote, M.; Rogers, J.; Meadows, M. E. (South African Geographical Journal, 1997)
Sediment cores, from the inner shelf off the Namaqualand continental shelf have been examined using radiographic and grain-size techniques. Size-frequency distributions reveal that the sediments are poly modal, with a dominant very fine-silt mode being between 8-4μm, and suggest that the weak, poleward-flowing De Decker Current causes southward dispersal of terrigenous mud off the Orange River mouth. It appears that this current is not strong enough to transport material coarser than very fine silt. Material >63μm in size is rare, but may be indicative of storm events. Quartz and mica in the sediments are related to the semi-arid climate of Namaqualand, where they are entrained by adiabatic Berg winds moving offshore from the interior. Sponge spicules indicate the presence of filter-feeding animals (epifauna). Planktonic foraminifera may be indicative of relatively high productivity associated with nutrient-rich upwelling waters, which support an enormous population of plankton. The presence of faecal pellets is associated with the presence of burrowing infauna. Authigenic gypsum is associated with the presence of anaerobic conditions in the sediments. Two of the lithofacies identified in these fine-grained deposits are: (a) laminated mud and (b) homogeneous mud. Primary sedimentary structures are present, particularly in the portion of the mudbelt closest to the Orange Delta, where the mud is well laminated. Laminations decrease in abundance southward from the delta, where the muddy sediment is increasingly bioturbated (burrowed) by infauna, probably by polychaete worms.
id: 218